Mad love - Dini, Paul (A Batman novel, 2019)
When she was only seven years old, Harleen Quinzel witnessed her father being beaten up by thugs, and then arrested by the police. That night she ran away to the safest place she could think of: Coney Island amusement park. But there, pursued into the Funhouse by the men who brutalised her father, she beheld unimaginable horrors. Years later, Harleen has put her past behind her, and used her intelligence and ambition to escape her childhood of poverty with a career in psychiatry. Assigned to her first position at Arkham Hospital, she will discover, deep in the asylum, something dangerous and alluring, something quite unlike anything else she has ever known before: The Joker. Because why would you settle for love, when you could have MAD LOVE? From the moment that Harleen finds a rose on her desk, to the moment she dons her harlequin hat, this is the definitive story that chronicles the obsession, the burning desire, the manic laughter, and the birth of one of the most controversial and popular comic book supervillains ever created: Harley Quinn.